USING DIGITAL MARKETING TOOLS IN SPORTS CLUBS WEBSITES (Fiep Bulletin - online, 2014)
The development of technology and social media has changed our daily lives. Post- digital sports clubs evolved to provide, by digital platforms, different forms of interaction and experience to fans, a phenomenon that already took scientific attention (Beech et al., 2000; Ioakimidis2010; Hur, Ko & Claussen, 2012). In this scenario, the website saw a big change with the emergence of social networks and new ways of using web, while reinvents itself to correspond to the fan’s needs. The incorporation of digital marketing tools in sports websites is a result of this reinvention. This work investigates how the 20 soccer clubs from Brasileirão Série A 2013 use the digital marketing tools on their websites to offer content and promote interaction with the fan. The method comprises a checklist of 32 implementable tools on the platform, categorized a priori in accordance to the given literature. The results shows that few clubs are using more than 50% of all digital marketing tools searched in their websites and that the ‘ease of use’ dimension is the most present. From this work, sports professionals can benefit from the information regarding the functionality of the website platform and marketing tools, as seen with Brazilian sports clubs.
Keywords: Sports marketing; sports website; Sports management